NLRP3 inflammasome activation downstream of cytoplasmic LPS recognition by both caspase‐4 and caspase‐5. Issue 10 (24th August 2015) - Baker, Paul J.; Boucher, Dave; Bierschenk, Damien; Tebartz, Christina; Whitney, Paul G.; D'Silva, Damian B.; Tanzer, Maria C.; Monteleone, Mercedes; Robertson, Avril A. B.; Cooper, Matthew A.; Alvarez‐Diaz, Silvia; Herold, Marco J.; et al.
<x xml:space="preserve">Abstract</x> Humans encode two inflammatory caspases that detect cytoplasmic LPS, caspase‐4 and caspase‐5. When activated, these trigger pyroptotic cell death and caspase‐1‐dependent IL‐1β production; however the mechanism underlying this process is not yet confirmed. We now show that a specific NLRP3 inhibitor, MCC950, prevents caspase‐4/5‐dependent IL‐1β production elicited by transfected LPS. Given that both caspase‐4 and caspase‐5 can detect cytoplasmic LPS, it is possible that these proteins exhibit some degree of redundancy. Therefore, we generated human monocytic cell lines in which caspase‐4 and caspase‐5 were genetically deleted either individually or together. We found that the deletion of caspase‐4 suppressed cell death and IL‐1β production following transfection of LPS into the cytoplasm, or in response to infection with Salmonella typhimurium. Although deletion of caspase‐5 did not confer protection against transfected LPS, cell death and IL‐1β production were reduced after infection with Salmonella. Furthermore, double deletion of caspase‐4 and caspase‐5 had a synergistic effect in the context of Salmonella infection. Our results identify the NLRP3 inflammasome as the specific platform for IL‐1β maturation, downstream of cytoplasmic LPS detection by caspase‐4/5. We also show that both caspase‐4 and caspase‐5 are functionally important for appropriate responses to intracellular Gram‐negative bacteria.